INNOVATION OF BUSINESS AND ENVIRONMENTAL PERFORMANCE IN KEBON INDAH BATIK ASSOCIATION KLATEN: THE IMPACT OF TRANSFER OF KNOWLEDGE AND QUALITY MANAGEMENT - Sulistyowatie, Syska Lady; Pahlevi, Reza Widhar (Jurnal Manajemen Bisnis, 2019)
The creation of environmental performance is not only influenced by aspects of innovation but also the need for quality management to improve competitiveness and create competitive advantage. This research was conducted at the Kebon Indah Batik Association in Bayat, Klaten, Central Java. Kebon Village is one of the centers of written batik using natural dyes. At present, five batik groups have been formed, consisting of 169 members, including Sidoluhur, Nusa Indah, Nuju Makmur, Sido Makmur, and Tsp Mukti and this research is aimed at determining the effect of knowledge transfer and quality management on environmental performance through innovation. This study uses primary data sources namely all members of the Kebon Indah Batik Association in Bayat, Klaten, Central Java. The data collection at an early stage were collected through an independent questionnaire, to analyze the conditions of the organization mapping, especially relating to the transfer of knowledge, quality management of environmental performance through innovation. The data was analyzed by using SPSS Path Analysis model. The results of the study showed that knowledge transfer and quality management influence environmental performance and innovation. Innovation has an influence on environmental performance. Based on the results of the path analysis that there is an influence between knowledge transfer on environmental performance through innovation and there is an influence between quality management on environmental performance through innovation. Innovation bridges the role of knowledge transfer on environmental performance.